RELATIONSHIP BETWEEN COMPLIANCE AND RELAPSE IN EARLY PSYCHOSIS PATIENT IN SPECIAL DISTRICT YOGYAKARTA (D.I.Y) - , NOR FAIRUZAIMI BINTI ZAKARIA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background Early psychosis is an important phase in psychotic disorders, with early management has been shown to be very helpful in reducing the rate of relapse. One of the key in the management of patients with early psychosis is ensuring their compliance towards medication they are prescribed with. Objective To determine whether there exist a relationship between compliance and relapse in early psychosis patients in Special District Yogyakarta (D.I.Y). Method Cross-sectional non-experimental quantitative study is done on 100 early psychosis patients gathered from selected hospitals in Yogyakarta in the period of March 2010 to March 2011. Result There is significant difference (p<0,05) in the degree of compliancy with the rate of relapse. The wide range in the 95% CI (0.002-0.0078) shows great uncertainty between the two variables in this study â compliance and relapse. Although data shows these two variables being positively correlated, the strength of the relationship is weak (CC = 0,234). Conclusion There is a relationship between compliance and relapse in early psychosis patients in Special District Yogyakarta (D.I.Y). Despite the weak correlation, there is still higher prevalence of relapse among patients that does not comply to their treatment.